Spiritual-Based Entrepreneurship in Pesantren: A Case Study of Pesantren Riyadlul Jannah’s Economic Movement - Santoso Budiyono (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Pesantren possess significant potential within the national economy, particularly through the development of entrepreneurship-based economic self-reliance. A notable example of success is Pesantren Riyadlul Jannah in Mojokerto, which has effectively established a sustainable business ecosystem. This research aims to explore the unique motivations driving entrepreneurial success within this pesantren, examining how their core values and beliefs are manifested in their business practices. Employing a qualitative methodology with a Grounded Theory approach, this study developed theory based on empirical data collected directly from the field. Data were gathered through in-depth interviews, participatory observation, document analysis, and audio-visual methods. Participants were selected using purposive and snowball sampling techniques, encompassing pesantren leader, business unit managers, students, and other stakeholders. The findings revealed that entrepreneurial motivation at Pesantren Riyadlul Jannah was driven by distinctive Islamic values, namely jihad, dakwah, and wathaniyah. Jihad encouraged students to build economic self-reliance to uphold Islamic values and enhance community welfare. Dakwah instilled a strong work ethic and a spirit of community empowerment, while wathaniyah fostered active involvement in managing national resources to achieve national economic independence. This study underscores the pivotal role of spiritual values as a primary factor in pesantren entrepreneurship. In contrast to conventional theories, these findings demonstrate that religious values shape the mindset and business strategies of pesantren entrepreneurs. Beyond its role as an educational institution, the pesantren also serves as a center for Islamic-based economic empowerment.